2003
DOI: 10.1189/jlb.0103024
|View full text |Cite
|
Sign up to set email alerts
|

Many chemokines including CCL20/MIP-3α display antimicrobial activity

Abstract: Previous studies have demonstrated that beta-defensins exhibit chemotactic activity by sharing the chemokine receptor CCR6 with the CC chemokine ligand CCL20/macrophage-inflammatory protein-3alpha (MIP-3alpha). Structural analysis of CCL20/MIP-3alpha revealed that most of the positively charged residues are concentrated at one area of its topological surface, a characteristic considered to be important for the antimicrobial activity of defensins. Here, we report that similar to defensins, CCL20/MIP-3alpha has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
469
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(477 citation statements)
references
References 40 publications
7
469
1
Order By: Relevance
“…The exact mechanism by which MIP-3α exhibits its anti-viral activity is not known, however the high isoelectric point (pI>10.6) and specific distribution of positively charged residues suggests a direct interaction with the negatively charged viral envelope. 8,9,23 The current study demonstrates that chemokines such as MIP-3α exhibits anti-viral activity against VV and further demonstrates a role for MIP-3α in controlling VV pathogenesis. Additionally, we demonstrate that insufficient expression and production of MIP-3α in AD skin increases the potential for disseminated VV infection following smallpox vaccination.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The exact mechanism by which MIP-3α exhibits its anti-viral activity is not known, however the high isoelectric point (pI>10.6) and specific distribution of positively charged residues suggests a direct interaction with the negatively charged viral envelope. 8,9,23 The current study demonstrates that chemokines such as MIP-3α exhibits anti-viral activity against VV and further demonstrates a role for MIP-3α in controlling VV pathogenesis. Additionally, we demonstrate that insufficient expression and production of MIP-3α in AD skin increases the potential for disseminated VV infection following smallpox vaccination.…”
Section: Discussionmentioning
confidence: 97%
“…9,11,23 Using gene chip microarrays, we previously observed elevated expression of MIP-3α in the lesional inflamed skin of psoriasis patients as compared to inflamed skin lesions from AD patients. 4 We confirmed this observation in the current study using real-time RT-PCR and immunohistochemistry which have a higher degree of sensitivity and reproducibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCL20/MIP-3␣, another previously unknown Candida-regulated endothelial chemokine, belongs to a subgroup of chemokines with defensin-like antimicrobial activity (29) and is a potent chemoattractant for dendritic cell precursors. CCL20/MIP-3␣ thus has the properties to act as a danger signal, thereby linking the innate to the adaptive immune system (30), which both determine the course of Candida infection in hosts (31).…”
Section: Discussionmentioning
confidence: 99%
“…The functions of antimicrobial factors in host defense are multi-faceted and range from direct killing of invading microbes (bacteria, fungi, and viruses) to linking innate and acquired immunity. 9,10 We and others have previously shown that epithelial cells in the FRT secrete factors that exhibit potent antimicrobial activity and include human α-defensin-5 (HD5), β-defensins 1-4 (HBD1-4), and secretory leukocyte protease inhibitor (SLPI). [11][12][13] These antimicrobial polypeptides, some of which are induced in response to PAMP exposure, are effective at inhibiting Gram-positive and Gram-negative bacteria, fungi, and enveloped viruses, including Neisseria gonorrhoeae, Chlamydia trachomatis, Candida albicans, Herpes Simplex Virus-2, and Human Immunodeficiency Virus-1.…”
Section: Introductionmentioning
confidence: 99%